2009
DOI: 10.1007/s00024-008-0438-1
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Joint Inversion of Teleseismic Waveforms for Earthquake Source Models Using Deep Ocean Bottom Pressure Records: A Case Study of the 2006 Kuril Megathrust Earthquake

Abstract: Abstract-The importance of accurate tsunami simulation has increased since the 2004 Sumatra-Andaman earthquake and the Indian Ocean tsunami that followed it, because it is an important tool for inundation mapping and, potentially, tsunami warning. An important source of uncertainty in tsunami simulations is the source model, which is often estimated from some combination of seismic, geodetic or geological data. A magnitude 8.3 earthquake that occurred in the Kuril subduction zone on 15 November, 2006 resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Offshore tsunami observations by OBP gauges such as the DART and the seafloor-cabled systems have been very useful with their high signal-to-noise ratios. Several studies have shown benefits of using the deep-sea tsunami records with seismograph data to investigate seismic/ tsunami sources [e.g., Ritsema et al, 1995;Baba et al, 2009;Yamazaki et al, 2011;Yokota et al, 2011]. For typical interplate, megathrust earthquakes that involve relatively simple mechanisms, the slip distributions can be well constrained by tsunami data alone [e.g., Fujii and Satake, 2006;Tang et al, 2009;Gusman et al, 2013].…”
Section: Summary and Remarksmentioning
confidence: 99%
“…Offshore tsunami observations by OBP gauges such as the DART and the seafloor-cabled systems have been very useful with their high signal-to-noise ratios. Several studies have shown benefits of using the deep-sea tsunami records with seismograph data to investigate seismic/ tsunami sources [e.g., Ritsema et al, 1995;Baba et al, 2009;Yamazaki et al, 2011;Yokota et al, 2011]. For typical interplate, megathrust earthquakes that involve relatively simple mechanisms, the slip distributions can be well constrained by tsunami data alone [e.g., Fujii and Satake, 2006;Tang et al, 2009;Gusman et al, 2013].…”
Section: Summary and Remarksmentioning
confidence: 99%
“…Similarly, if the actual slip was underneath dry land, instead of the open ocean, that could also cause a substantial change in the tsunami amplitude, even on the coast of Queensland. However, we believe that the teleseismic rupture model we obtained here should have been enough to simulate the tsunami, based on the results from a previous study of the 2006 Kuril Islands earthquake (BABA et al, 2008).…”
Section: Differences In Maximum Amplitudementioning
confidence: 99%
“…Moderate‐amplitude tsunamis were produced around the Pacific by the two earthquakes [ Rabinovich et al , 2008; Tanioka et al , 2008; Fujii and Satake , 2008; Baba et al , 2009]. Observed tsunami heights at remote distances were less than 1.2 m for the 15 November 2006 event [ Rabinovich et al , 2008], except for a 1.76 m wave that destroyed two docks and damaged another in Crescent City, California [ Kowalik et al , 2008; Horrillo et al , 2008].…”
Section: Introductionmentioning
confidence: 99%